PENGARUH PROFESIONALISME PENGELOLAAN ASET DESA, OPTIMALISASI PEMANFAATAN ASET DESA DAN PEMBERDAYAAN MASYARAKAT TERHADAP PENDAPATAN ASLI DESA (STUDI EMPIRIS PADA DESA DI KOTA BANDA ACEH) - Istiqamah, Istiqamah; Bustamam, Bustamam (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2021)
This study aims to examine the effect of Professionalism in Village Aset Management, Optimization of Village Aset Utilization, and Community Empowerment together and partially on Village Original Income in Banda Aceh City. Based on 94 questionnaires distributed to respondents, using the Simple Random Sampling technique and analyzed using multiple linear regression models, the results showed that together all the variables in this study had an effect on Village Original Income. Then partially the variables of Professionalism in Village Aset Management and Community Empowerment have an effect on Village Original Income. while the Village Aset Utilization Optimization variable has no effect on Village Original Income in Banda Aceh City.